Identification of Pests and Deseases on Chrysanthemum in Nglurah Village, Tawangmangu - Anas Pratiwi; Gilang Bayu Saputro; Nadya Ayu Dewantari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Chrysanthemum (Dendrathema grandiflora Tzvelev syn. Chrysanthemum murifolium Ramat) is one of the cut flowers and potted flowers favored by the public, especially the upper middle class and ornamental plants. Chrysanthemum is a commercial plant that is easy to grow and cultivate. Pests and diseases are one of the problems in the development of chrysanthemum cultivation. This research is located in the area of Sewu Kembang Agro Tourism, Nglurah, Tawangmangu, Karanganyar Regency. This research was conducted from September 4 to October 2, 2021. This research was carried out for 29 days using 10 samples of potted chrysanthemums. The tools used include other cameras to take pictures and stationery to record data. The variables observed were pests and diseases that attack chrysanthemum plants. In this study using direct observation of the owners of potted chrysanthemums. The data obtained were analyzed descriptively qualitatively. The result of this study found pests that attack potted chrysanthemums, namely leaf miners (Liriomyza sp.) and soil caterpillars (Agrotis ipsilon). While for disease attacks caused by several types of fungi that cause diseases as follows leaf rust disease, gray mold disease, and oidium powder disease.